Pengaruh Inflasi, Pertumbuhan Ekonomi dan Investasi terhadap Pengangguran di Indonesia, 2001-2010 - Rusmusi Indranjoto; Agustin Susyatna Dewi (EKO-REGIONAL, 2012)
The purposes of this research are to analyze the influence of inflation, economic growth and investment partially and simultaneously toward unemployment. The research is conducted with quantitative analysis based on multiple regression analysis. The result shows that by partially inflation, economic growth and investment have no influence toward dependent variables (unemployment). Based on the test result of f-test simultaneously, it can be concluded that inflation, economic growth, and investment concomitantly have not significantly effect to total unemployment rate in Indonesia. Keywords:   inflation, economic growth,investment, unemployment